Use of Misoprostol in Term pregnant women for Good Delivery Outcome: Experience at a tertiary care Hospital in Dhaka (Journal of Science Foundation, 2016)
Background: Use of misoprostol in term pregnancy is very useful for the better outcome during delivery. Objective: The purpose of the present study was to see the delivery outcome among the term pregnant women. Methodology: This cohort study was carried out in the Department of Obstetrics and Gynaecology at Sir Salimullah Medical College and Mitford Hospital during the period from 1 st September 2005 to 28th February 2006. Primi or second gravida patients with the gestational age between 37 weeks to 42 weeks in singleton pregnancy with cephalic presentation and not in labour who came for delivery purposes during the study period at any age were selected as study population. After proper selection of the cases, induction of labour (IOL) was done by applying Tab Misoprostol 50mcg in the posterior vaginal fornix. Purpose of induction of labour was successful when vaginal delivery occurred without any untoward side effects and without any surgical interference. Result: Out of 60 pregnant women 21 (35%) patients had unfavourable Bishops' score with 3-5 and 39 (65%) patients had favorable Bishops' score with 6-10. 39 patients had favourable pre- induction cervical score, among them 79% had delivered vaginally and 21% had undergone LUCS. 21 patients had unfavourable cervix, among them 57% experienced vaginal delivery and 43% experienced LUCS. Out of all study population 60% of study population who were primigravide had vaginal delivery in 67% cases and caesarean section in 33% cases and among 40% 2nd gravida cases vaginal delivery was 79% and caesarean delivery was 21%. Conclusion: In conclusion the use of misoprostol during term pregnancy is significantly related with the normal delivery.Journal of Science Foundation 2014;12(2):22-26DOI:  http://dx.doi.org/10.3329/jsf.v12i2.27733